Incidence, risk factors and outcomes of preterm live births in a tertiary health facility in Ghana - Anthony Kwame Dah; Joseph Osarfo; Hintermann Mbroh; Gifty Dufie Ampofo; Adu Appiah-Kubi; Wisdom Klutse Azanu; Michael Amoh; Emmanuel Senanu Komla Morhe (PLoS ONE, 2025)
Objectives Accurate measures of the burden of preterm live births are a challenge, particularly in low-and-middle income countries, due to factors including poor data quality and unreliable methods using last menstrual period (LMP) in determining gestational age of pregnancies. This study employed gestational age from first trimester ultrasound to determine incidence of preterm livebirths at Ho Teaching Hospital in Ghana, their risk factors and adverse outcomes. Methods This was a prospective study involving 666 pregnant women and their 680 live newborns from 1st October, 2019–31st March, 2020. Data was collected on socio-demographic characteristics such as age and for other variables including gestational age at delivery and birthweight. The primary outcome was overall preterm livebirth incidence. Logistic regression analysis was used to determine its predictors. Odds ratios were reported with 95% confidence intervals. Statistical significance was pegged at p-value <0.05. Results The mean age of the women was 29.0 years. About 93% (616/666) had formal education. Overall preterm livebirth incidence was 9.1% (62/680). Formal employment [AOR 6.84 (95% CI 1.63–28.73), p = 0.009], informal employment [AOR 4.98 (95% CI 1.39–17.85), p = 0.014] and hypertensive disorders in pregnancy (HDP) [AOR 6.43(95% CI 2.78–14.89); p < 0.001] increased the odds of preterm livebirth. Adequate antenatal clinic contacts (ANC) [AOR 0.14 (95% CI 0.05–0.37), p < 0.001] and doses of sulphadoxine-pyrimethamine for malaria prevention in pregnancy (IPTp) [AOR 0.21(0.10–0.45), p < 0.001] reduced the odds of preterm livebirth by 86% and 79% respectively. Conclusion Overall preterm livebirth incidence in the study compared favourably with global estimates. HDP and being employed were important risk factors and. suggest reducing workloads of pregnant women in formal employment may be beneficial. Targeted posting of specialists to aid adequate management of HDP at district hospitals and mitigating missed opportunities for IPTp need to be considered.